Frameworks of place. From revealed patterns to imposed patters - Gómez García, Alejandro (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
The proximity between the terms trace and pattern suggests the possibility to understand one as part of the other. In other words, trace may be thought as a fragment, vestige, or matrix of a possible geometric grid specific and characteristic of a particular place. Either when conceived as the result of certain pre-existing structures, natural or artificial, or when established from conditions outwit specific situations, pattern may act as a regulating guide during the architectural design process, guaranteeing both the unity of the whole and the integration between architecture and place. Rooted on a concise reflection of some of the most distinctive architectural proposals from the 1950’s and 1960’s, which apply grids or patterns as a fundamental compositional tool, and coinciding with the period in which the concept of the mat-building emerges forcefully in the heart of the first discussions of Team X, this paper outlines a possible framework of reference between the concepts of revealed pattern and imposed pattern, as an aid to the study of this approach to architectural design